Study of Electrical System Analysis of the Cadet Dorm Building of the West Sumatra Snailing Polytechnic - Muchtar, Niko Zainudin; Rauf, Rosnita; Anshar, Chairul Nazalul (Dinasti Publisher, 2025)
The quality of electrical installations is highly dependent on the implementation and application of electrical installation standards, namely PUIL 2011 (General Requirements for Electrical Installations) and other supporting regulations. The implementation is to ensure the safety of humans, tools, and buildings, as well as the main requirement for electrical installations to be carried out safely, reliably, and environmentally friendly. So it is necessary to conduct an evaluation of the electrical system to ensure the safety, reliability, and efficiency of the system are in accordance with electrical installation standards. In the cadet dormitory building, there are several rooms that function as bedrooms, living rooms, pantries, warehouses, and toilets with an electrical system consisting of power outlets, lighting installations, and air conditioning. Based on the results of the study, the total installed load of LVMDP is 104,134 Watts using a 3-phase 250A MCCB with a cable size of 4x240 mm2 NYFGbY. The 1st floor AC panel has a total load of 27,360 Watts using a 3-phase 80A MCCB using a cable of 4x35 mm2 NYY. Lighting Panel & Socket on the 1st floor total load of 9,762 Watts using 3 phase 40A MCB using 4x16 mm2 NYY cable. AC Panel on the 2nd floor total load of 27,360 Watts using 3 phase 80A MCCB using 4x35 mm2 NYY cable. Lighting Panel & Socket on the 2nd floor total load of 5,473 Watts using 3 phase 20A MCB using 4x4 mm2 NYY cable. AC Panel on the 3rd floor total load of 27,360 Watts using 3 phase 80A MCCB using 4x35 mm2 NYY cable. Lighting Panel & Socket on the 3rd floor total load of 6,819 Watts using 3 phase 32A MCB using 4x6 mm2 NYY cable